STORY TELLING ACTIVITY COUNSELING AS AN EFFORT TO DEVELOP PUBLIC SPEAKING POTENTIAL IN ELEMENTARY SCHOOL STUDENTS - Amalia Rahma Karim; Amelia Nur Rahmawati; Lidya Anastasya Ginting; Sri Sobiyah (Yayasan Putra Adi Dharma, 2024)
The service is carried out on elementary school students, where the purpose of this service is to increase students to be able to appear brave and become the next generation who are active, creative, and think critically. Elementary school students are the alpha generation who are born, grow and develop in the era of increasingly sophisticated and modern developments in science and technology. This generation is accustomed to the ease of doing all activities. Therefore, the application of learning using the story telling method is carried out to increase the potential for improving public speaking of students of SDN Mekarmukti 01 Cikarang Utara, Bekasi Regency. The results of the service include the following: Participatory Action Research (PAR) method is used, which includes socialization, implementation, supervision, and evaluation. The service results show that the story learning method increases students' courage to speak in public. 95% of students can answer sheet questions quickly and correctly. Four students from each group have the ability to creatively and confidently retell stories about Indonesian subjects using the story method.